2008
DOI: 10.1093/annonc/mdm538
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CA 15-3 and CEA serum levels as predictor for breast cancer outcomes

Abstract: High preoperative CA 15-3 and CEA levels may reflect tumor burden and are associated with advanced disease and poor outcome. Measuring preoperative levels of CA 15-3 and CEA can be helpful for predicting outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
94
4
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 31 publications
10
94
4
7
Order By: Relevance
“…Previous studies have suggested that elevated serum levels of CA 15-3 and CEA preoperatively were significantly associated with tumor size, axillary node metastasis and advanced stage in the multivariate analysis; in addition, patients with elevated CA 15-3 and CEA levels exhibited a worse prognosis compared to those with normal levels of CA 15-3 and CEA, even in stage-matched analysis (6,7). Recent studies demonstrated that serial determination of CA 15-3 and CEA levels during the postoperative follow-up of breast cancer patients may be useful for early detection of preclinical recurrence or metastatic disease (8,9).…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies have suggested that elevated serum levels of CA 15-3 and CEA preoperatively were significantly associated with tumor size, axillary node metastasis and advanced stage in the multivariate analysis; in addition, patients with elevated CA 15-3 and CEA levels exhibited a worse prognosis compared to those with normal levels of CA 15-3 and CEA, even in stage-matched analysis (6,7). Recent studies demonstrated that serial determination of CA 15-3 and CEA levels during the postoperative follow-up of breast cancer patients may be useful for early detection of preclinical recurrence or metastatic disease (8,9).…”
Section: Introductionmentioning
confidence: 83%
“…The results of other authors regarding the relationship between diseases stage and the level of tumour markers are discordant. Some authors have reported more frequent occurrence of the elevated plasma levels of these tumour markers in more advance stages of that disease but others have reported lack of statistical relation between serum levels of these markers with disease stage [11]. Moreover the preoperative serum CA 15-3 level is useless for determining the histologic grade of the tumor [3].…”
Section: Discussionmentioning
confidence: 99%
“…And MUC-1, which is one of cell surface associated mucin, is aberrantly over expressed in many adenocarcinomas especially breast cancer. Therefore, higher level of CA15-3 may be associated with larger burden of occult disease and poor outcome (Park et al, 2008). Carcinoembryonic antigen (CEA) is the most widely used marker in monitoring the clinical course of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%